2021
DOI: 10.15633/pch.3894
|View full text |Cite
|
Sign up to set email alerts
|

Relational Family Therapy in the Treatment of Sudden Cardiac Arrest Survivors and their Relatives

Abstract: Sudden cardiac arrest is the most common single cause of death in the contemporary world, but the proportion of survivors is increasing thanks to modern intensive methods of hospital treatment. However, data show that survivors experience high rates of neurological and cognitive deficits and poorer emotional well-being, which is a major challenge in treating these individuals and encouraging their integration in everyday life. These issues range from a number of emotional problems, such as anxiety and depressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Previous studies showed, that families of patients with acute syndromes (e.g. myocardial infarction) show psychological distress [7,[20][21][22][23]. Witnessing an ambulance team performing CPR on relatives is associated with an increased risk of depression 90 days after the event [24].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed, that families of patients with acute syndromes (e.g. myocardial infarction) show psychological distress [7,[20][21][22][23]. Witnessing an ambulance team performing CPR on relatives is associated with an increased risk of depression 90 days after the event [24].…”
Section: Discussionmentioning
confidence: 99%
“…Signs of pathological psychological processing might occur only a short time but might also continue over longer periods influencing the life of this person in multiple aspects [7]. In a study by Van't Wout Hofland one out of three caregivers of survivors after cardiac arrest experienced high level of trauma related stress even two years after the event.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While little is known about the psychological impact of witnessing brain injury, evidence from literature on effects of OHCA indicates that bystanders might be deeply traumatized; one study found that more than one in three bystanders experienced "pathological psychological processing" weeks following OHCA independent of age or personal relationship to the index patient. [136][137][138] These issues demand further empirical study and the appropriate resources to help bystanders adapt to psychological distress. Further research, education, and capacity-building are needed in these areas to advance responsible systems of hyperacute DoC care.…”
Section: Hyperacute Phasementioning
confidence: 99%